Home run : baseball's greatest hits and hitters - Hollander Zander; Hollander, Zander (New York : Random House, 1984)
A collection of anecdotes and facts about home runs and their hitters including such aspects as length of hits, grand slams, biographical sketches of famous hitters, and team efforts.
Rev. ed. of: The Home run book. 1981.
"A Zander Hollander sports book."
Includes index.
Keywords: Batting (Baseball); Baseball players -- United States; Baseball -- United States; Home runs (Baseball); Baseball; Baseball players